A fixed point index approach to Krasnosel'skiĭ-Precup fixed point theorem in cones and applications. (January 2023) - Rodríguez–López, Jorge
Abstract: We present an alternative approach to the vector version of Krasnosel'skiĭ compression–expansion fixed point theorem due to Precup, which is based on the fixed point index. It allows us to obtain new general versions of this fixed point theorem and also multiplicity results. We emphasize that all of them are coexistence fixed point theorems for operator systems, that means that every component of the fixed points obtained is non-trivial. Finally, these coexistence fixed point theorems are applied to obtain results concerning the existence of positive solutions for systems of Hammerstein integral equations and radially symmetric solutions of ( p 1, p 2 ) -Laplacian systems.